PENGELOLAAN RISIKO BENCANA BANJIR: STRATEGI AKUNTANSI UNTUK PEMULIHAN EKONOMI DI KOTA MEDAN, SUMATERA UTARA - Harningsih Fitri Situmorang (Universitas Islam Negeri Sumatera Utara Medan, 2026)
Medan City, as the capital of North Sumatra, is highly susceptible to perennial flood disasters that pose significant fiscal risks and economic disruption. This study examines the strategic role of public sector accounting in mitigating economic impacts and facilitating post-disaster recovery in Medan. Adopting a Systematic Literature Review (SLR) methodology, the research synthesizes academic journals and official reports published between 2020 and 2025. The analytical framework incorporates the Value for Money (VFM) principle, economic vulnerability analysis, and emergency fund effectiveness models. The findings reveal that the economic causes of flood impacts are rooted in high vulnerability within MSME clusters and inadequate asset impairment records. Strategic management through the optimization of Unexpected Expenditures, simplified bureaucratic accounting for aid distribution, and the implementation of disaster-risk-based budgeting is essential. This study concludes that disaster accounting acts as a vital pillar for regional fiscal resilience and public accountability, ensuring sustainable economic recovery for the people of Medan